Checklist of genus- and species-group names of the false limpets Siphonaria (Mollusca: Gastropoda: Euthyneura) - White, Tracy R.; Dayrat, Benoît (Zootaxa, 2012)
Not since Hubendick’s 1946 Systematic Monograph of the Patelliformia has a comprehensive taxonomic work been com-pleted on the genus of false-limpets Siphonaria, distributed worldwide, except in the northern Atlantic. A checklist of allsupra-specific names associated with Siphonaria is established. A checklist of all species-group names is provided as welland their nomenclatural status is discussed (available, not available, permanently invalid). Of the 270 species-group namesincluded in the checklist, 205 are available and not permanently invalid. All other names are either not available or avail-able but permanently invalid. The geographic distribution of the type localities is also presented; of the 205 species-group names that are available and not permanently invalid, 62 are from the tropical and subtropical Indo-West Pacific.